Îngropat în cer: Imre Kertész, Kadiș pentru copilul nenăscut - Cristina Deutsch (Revista de Istorie și Teorie Literară)
2002 Nobel Literature Prize Winner, Imre Kertész, in his novel Kaddish for an Unborn Child, configures a path of Jewishness as “reconceptualization of the future” caused by the traumatic postHolocaust historical circumstances. Denying the possibility of giving birth to a child is an issue entwined with the idea of the auctorial self release by using the compulsory recording on paper as a genuine weapon of memory. The article examines both the problems of the literary text as such, the authenticity of the novel, and the hero’s evolution from a traumatic childhood to the survivor’s adulthood, analyzing the complexity of his passage through the triad “birth / life / death”, each of these instances being mirrored in multiple manners by the characters’ denial of assuming his own emptied of meaning Ego being “thrown into the world”.